Impact of the No Early Release Act (NERA) on Prosecution and Sentencing in New Jersey, 1996-2000 - McCoy, Candace ([Verlag nicht ermittelbar], 2005)
This study examined New Jersey's No Early Release Act (NERA), which became effective in 1997. NERA required that offenders convicted of violent crimes serve at least 85 percent of their sentences before becoming eligible for parole. This study's primary goal was to determine whether prosecutors changed their charging and plea bargaining practices in order to obtain sentences under NERA that were roughly equivalent to those imposed before NERA. Data were obtained from the New Jersey Administrative Office of the Courts for 1996 to May 2000. These data included every case in which a crime covered by the No Early Release Act was charged and, for comparison, every case involving a burglary charge, a charge not covered by NERA. These data cover defendants' progress through the New Jersey court system, including the initial charge, indictment, and sentencing.